Adipose tissue expression of CCL19 chemokine is positively associated with insulin resistance - Kochumon, Shihab (Diabetes Metab Res Rev, 2018)
BACKGROUND: Chemokines produced by adipose tissue (AT) are involved in the development of chronic low‐grade inflammation in obese humans and rodents. AT CCL19 expression in obesity and its association with metabolic inflammation and insulin resistance are poorly understood. This study aimed to investigate the effects of CCL19 gene expression on inflammatory markers in subcutaneous AT and insulin resistance. METHODS: Subcutaneous adipose samples were collected from 56 non‐diabetic (26—obese, 21—overweight, and 9—lean) individuals. Expression of CCL19 and inflammatory markers was determined using real‐time RT‐PCR. Plasma C‐reactive protein (CRP) and adiponectin were measured by ELISA. Insulin sensitivity was assessed using homeostasis model assessment index (HOMA). RESULTS: CCL19 expression was significantly higher in obese compared with lean individuals (P < 0.034). The elevated expression of CCL19 associated positively with body mass index (r = 0.253; P = 0.049). CCL19 expression correlated positively with IL‐8 (r = 0.39; P = 0.006), IL‐12 (r = 0.43; P = 0.003), IP‐10 (r = 0.25; P = 0.07), CCL5 (r = 0.37; P = 0.011), CCR2 (r = 0.44; P = 0.001), and CCR5 (r = 0.35; P = 0.009). Additionally, CCL19 was positively correlated with triglycerides (TG: r = 0.41; P = 0.001), fasting blood glucose (FBG: r = 0.49; P < 0.0001), glycated haemoglobin (HbA1c: r = 0.396; P = 0.001), and CRP (r = 0.387; P = 0.019) whereas it had negative association with HDL cholesterol (r = −0.282; P = 0.035) and adiponectin (−0.393; P = 0.019). Notably, HOMA‐IR correlated positively with CCL19 (r = 0.38; P = 0.01). In multiple regression analysis, CCL19 is an independent predictor of IL‐8 and IL‐12. CONCLUSIONS: These data demonstrate that increased AT expression of CCL19 in obesity may represent a molecular link between metabolic inflammation and insulin resistance.